Using Storytelling Technique to Improve Reading Ability at the Seventh Grade Students Of SMP N 5 Jambi Academic Year 2017/2018 - Ratna Juleha, Suyadi, Nurul Fitri (JELT: Journal of English Language Teaching, 2018)
AbstractThe objective of this study was to find out the result of Using Story Telling technique To Improve Reading Ability at The Seventh Grade Students of SMPN 5 Jambi. The population of this research was all the seventh grade students of SMPN 5 Jambi which is grouped into ten classes. The class was taken as the sample was class VIIA consist of 33 students and VIIB consists 33 students by cluster sampling. The design of the research was experimental method. The research used two groups, experimental group and control group. Both of groups takes a pre-test and post-test. The researcher did two treatments for the sample. The objective of this study was to find out the result of Using Story Telling technique To Improve Reading Ability at The Seventh Grade Students of SMPN 5 Jambi. The population of this research was all the seventh grade students of SMPN 5 Jambi which is grouped into ten classes. The class was taken as the sample was class VIIA consist of 33 students and VIIB consists 33 students by cluster sampling. The design of the research was experimental method. The research used two groups, experimental group and control group. Both of groups’ take a pre-test and post-test. The researcher did two treatments for the sample.Keywords: Reading Ability, Storytelling Technique